Camera technology for monitoring marine biodiversity and human impact. Issue 8 (3rd October 2016) - Bicknell, Anthony WJ; Godley, Brendan J; Sheehan, Emma V; Votier, Stephen C; Witt, Matthew J
Abstract : Human activities have fundamentally altered the marine environment, creating a need for effective management in one of Earth's most challenging habitats. Remote camera imagery has emerged as an essential tool for monitoring at all scales, from individuals to populations and communities up to entire marine ecosystems. Here we review the use of remote cameras to monitor the marine environment in relation to human activity, and consider emerging and potential future applications. Rapid technological advances in equipment and analytical tools influence where, why, and how remote camera imagery can be applied. We encourage the inclusion of cameras within multi‐method and multi‐sensor approaches to improve our understanding of ecosystems and help manage human activities and minimize impacts.